About preparation for national Antarctic research in the middle of XX century (on the occasion of 60 years annivesary of The First Multipurpose Antarctic Expedition) - I. N. Sokratova; L. M. Savatyugin; И. Н. Сократова; Л. М. Саватюгин (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2016)
. .